Entre o visível e o enunciável em educação: o que pode uma docência que cava a si mesma? - Garlet, Francieli Regina (2018)
This dissertation considers teaching happening within the movement of digging itself along encounters that are produced with wanderings, readings, writings, images and educative experiences. A teaching process produced while one experiments being a teacher, but also while one writes/composes a dissertation with elements/fragments that do not necessarily relate to teaching or educative spaces fulfilled by it. This dissertation was composed by operating a process of ‘making holes’ (DELEUZE & GUATTARI, 1997) or subtraction, in Bene’s terms (DELEUZE, 2010), of a majoritarian notion of teaching, digging from within what the word ‘teaching’ is accustomed to reinforce. Therefore, the problem that moved the research invited us to think: What can the teaching digging holes in sayings and views which stratify it do? A wandering way of research (GARLET, 2014) embraced the idea of becoming moth in this investigative process. Thus, a researcher-moth- wanderer lurks (DELEUZE, 1988-1989) in teaching/life, what is composed by her body/thinking, potentializing her to dig/think other possible and impossible ways in teaching as she wrote/composed this dissertation. She operated with the notion of ‘empty’ and ‘outside’ through authors such as Blanchot (2005, 2010 and 2011), Foucault (2008), Deleuze (2006) and Levy (2011) and the notion of ‘minor’ (DELEUZE, 2010) and (DELEUZE & GUATTARI, 2014). She was interested in experimenting/digging empty spaces and offering the dissertation as an invitation to dig holes. She wanted to operate teaching and a ‘minor formation’ (RIBETTO, 2011), considering what sprouts incessantly, what escapes and can be invented in a continuum of experimentations/compositions with images, readings, educative experiences and writings. So, this dissertation was gaining consistency and presents here what has been produced along the triggers that activate a moth- wanderer-becoming in the researcher who, by digging holes in what is said and seen so that forms of being a teacher are prescribed or halted, tried to open singular possibilities of existence. This teaching, in the space and time of production of this dissertation, has experimented compositions with empty spaces, silence, noise, papers, kapoks, the city that gets old, the moth that digs/wanders, and cocoon in folds/works. Operations in handicrafts produced with images, writings, holes, silence, speed and slowness... in the hard copy of the dissertation as well as in the visual diaries produced with the intensities that allocate within being a teacher. This dissertation proposed to dig/establish a gerund teaching in the groggily steps of a teacher/researcher to be as an endless piece of work.